(untitled) (Global Journal of Human-Social Science, 2020)
India has an extremely rich craft tradition recognized by its unique aesthetic and mythological emotions expressed through artistry The history of Indian Handicrafts dates back to one of the earliest civilizations of the world It is now home to more than 7 3 million artisans residing mostly in rural or semi urban areas of India This study will give a clear perception of the target consumers behaviour towards purchasing Indian handicrafts and would help stakeholders involved in Indian handicraft sectors to leverage on the critical findings stated in this study and devise a holistic marketing platform to explore the mentioned market opportunities of Indian Handicrafts Certain critical challenges faced by this sector is inefficient institutional framework relevant education low capital and deprived exposure to new technologies no access to market intelligence The paper also highlights critical constraints found during market research from consumer end and also suggests strategies which can be adopted The study also focuses on strategic collaboration of artisans with designers tourism industry CSR tech start-ups NGOs market research firms SHG associations can bring the much awaiting change in this unorganised yet unexplored and lucrative sector of India